The impact of facilities management on students' academic achievement / Anom Munajat Zurainan, Eliy Nazira Mat Nazir and Sabiroh Md Sabri - Munajat Zurainan, Anom; Mat Nazir, Eliy Nazira; Md Sabri, Sabiroh (Universiti Teknologi MARA, Perlis, 2021)
Facilities management is one of the important aspects that need to be considered in every educational institution. Literature shows that good management of the facilities in an educational institution can affect students' learning process and subsequently impact the students' academic achievement. Thus, the educational institution must critically understand how to manage the facilities well. The purpose of this research is to investigate the management of various facilities and how it impacts students' academic achievement. This research was carried out in Universiti Teknologi MARA Perlis Branch with the main objective to investigate the management of facilities such as e-learning facility, classroom, library, and hostels and whether they have any effect on the students' academic achievement. Data was collected using questionnaires which were distributed to 217 students. Data were then analyzed using SPSS software and a few analyses were carried out such as descriptive analysis, correlations, and regression analysis. The results have shown that three areas of the facilities have a significant impact on students' academic achievement while only one area does not have a significant impact on students' academic achievement. The results of this study could be used by an educational institution to better plan and manage their facilities and subsequently help students to increase their academic achievement.